Notes on the Community of Goods: Basic Rules and Some Litigate Quarters - Pérez Vallejo, Ana María (2018)
Situations in which there is a community of goods or rights have been the subject of a copious source of conflicts. The theme proposed in this study, intends to analyze the ordinary community pro indiviso, figure clearly defined in the Spanish Civil Code (articles 392 to 406). However, these basic rules that order the relations between comuneros, co-owners or condominiums, although they are of an apparently simple approach, are complex from a practical perspective. The diversity of nuances to consider usually generates controversial issues, which will be addressed from a doctrinal and jurisprudential point of view. It is not the object of this paper to establish definitive conclusions, but to show some notes on the reality and practical application of the rules that discipline this old institution, which is at the service and solves daily problems in legal traffic.